2014
DOI: 10.1109/lwc.2014.2344656
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Analysis of Interference Alignment With Bounded CSI Uncertainty

Abstract: Interference alignment (IA) has been demonstrated to achieve the degree-of-freedom (DoF) of an interference channel given perfect global channel state information (CSI). In this letter, we consider the case of imperfect CSI with bounded errors and derive a capacity lower bound of the channel using IA. We show that this lower bound is within 1 bps/Hz of the capacity of the perfect CSI case up to a certain signal-to-noise ratio (SNR) which we refer to it as the saturating SNR. Further, we introduce a new metric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 15 publications
(18 reference statements)
0
28
0
Order By: Relevance
“…IA is a promising approach to increase the degrees-offreedom (DoF) of HetNets by aligning the interference from different transmitters into the same lower-dimensional interference subspace at each receiver [15]- [18]. IA concept originated from an elegant coding scheme for 2-user MIMO X channel [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IA is a promising approach to increase the degrees-offreedom (DoF) of HetNets by aligning the interference from different transmitters into the same lower-dimensional interference subspace at each receiver [15]- [18]. IA concept originated from an elegant coding scheme for 2-user MIMO X channel [15].…”
Section: Introductionmentioning
confidence: 99%
“…[16] and [17] studied the performance of wireless networks with Poisson clustered process (PCP) based on the probability generating function (PGF) where perfect intra-cluster channel state information (CSI) was available and the intra-cluster interference was completely eliminated by using the IA approach. Moreover, the case of imperfect CSI with bounded errors was considered in [18], and a capacity lower bound of the channel by using IA was derived. These traditional methods to implement IA may not be optimal to achieve the highest spectrum efficiency in the presence of the path-loss effect.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus indispensable to directly investigate the achievable rate of various IA schemes. The achievable rate of IA under imperfect CSI are investigated [11][12][13][14][15][16]. In [11], the impact of channel error on the achievable rate of IA was first investigated and closed-form lower and upper bounds of the sum mutual information of IA are derived.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the loss in sum rate is bounded by a constant if the error variance is proportional to the inverse the SNR, and thus the full DoF is achievable. Paper [13] studied the performance of IA with bound CSI errors, and tight lower bound was derived, but the upper bound was not considered. The work in [14] considered the scenario where the main channel CSI is perfect but the crosstalk CSI is in errors, and obtained a closed-form rate through analyzing the statistical distribution of the saturating SNR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation